SIGNIFIKANSI PERANGKAT IJTIHAD DALAM KAJIAN UṢHŪL FIQH - Muhammad Aziz (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Abstract. Islamic law contains all human benefits, both the benefit of the world andthe hereafter, the benefit of individuals and groups. Human welfare is regulated insuch a way through legal instruments and their arguments. Ijtihad is a term that isquite popular among Muslims, especially in the study of Islamic law. In today's era,there are many differences in Ma'hab in Islamic law caused by ijtihad. All of that cannot be separated from the results of ijtihad and all certainly strive to find the bestlaw. Precisely with ijtihad, Islam is more flexible, dynamic, flexible according to thedynamics of the times, and Islamic law is not silent in dealing with the increasinglycomplex problems of life. Ijtihad is an effort made by a faqih in earnest to extract asyara' law from detailed arguments. The laws of ijtihad vary according to theconditions faced by the mujtahids. Ijtihad is divided into several parts according tothe point of view, including in terms of the arguments that are used as guidelines, interms of its implementation, in terms of whether or not it is possible to stop ijtihadactivities, and in terms of the results achieved by ijtihad. The ijtihad method consistsof qiyas, istihsan, maslahah mursalah, istishab, 'urf, and sadd dzarai'. Ijtihad hascontinued to develop from the time of the Prophet Muhammad to the present day.Therefore, the historical description of ijtihad can serve as a benchmark to see theimportance of ijtihad's position in the present context which is marked by changes invarious fields of life.Keyword: Device, ijtihad, study of uṣūl fiqh